EVALUATION OF THE EFFICIENCY OF AGRICULTURAL PRODUCTION IN THE PIVOTAL FARMS UTILIZING REMOTE SENSING TECHNIQUES - Kadhim Sbahi, Muslim; Razzak Tarish Ziboon, Abdul; Ibrahim Hassoon, Khalid (Journal of Engineering and Sustainable Development, 2019)
Evaluation of the efficiency and estimating crop yield and forecasting is very important because relation to food security of the country and to reach the stage of self-sufficiency. Research is trying to estimate the crops and solve the problem of monitoring of farms inaccessible by field visits; monitor the implementation of the agricultural plan in addition, to monitoring the health status of crops. Utilizing the application of remote sensing RS, the geographical information system (GIS) added satellites imageries with multi-temporal and spatial analysis of vegetation cover. The research includes the collection of (12 images) Landsat8 and (3 images) Sentinel-2. In addition the meteorological data from agricultural meteorological stations of the Iraqi Ministry of Agriculture. Moreover the field data. Covered the winter planting season from 01/10/2015 to 01/05/2016. The research includes using the Cropwat program to calculate the Calendar germination of crops and using ERDAS IMAGINE 2014 to create process and calculation NDVI, Change Detection, and spectral profile analysis from imageries. Moreover using ArcGIS 10.3 for building Geodatabase, building the spatial database, analysis data, and product maps. The results of the evaluation showed that most of the Ain al-Tamur pivotal farms are highly efficient and the results of change detection for the NDVI and NIR are very effective.